A Draft Reference Genome Assembly of the Critically Endangered Black Abalone, Haliotis cracherodii. (14th May 2022) - Orland, Chloé; Escalona, Merly; Sahasrabudhe, Ruta; Marimuthu, Mohan P A; Nguyen, Oanh; Beraut, Eric; Marshman, Blythe; Moore, James; Raimondi, Peter; Shapiro, Beth
Abstract: The once abundant black abalone, Haliotis cracherodii, is a large, long-lived grazing marine mollusk that inhabits the rocky intertidal along the coast of California. The species has experienced dramatic declines since the mid-1980s largely due to the fatal bacterial disease called withering syndrome, leading to the collapse of an economically important fishery and to its inclusion into the IUCN listing as a critically endangered species. In some places impacted by the disease, populations of black abalone have declined by more than 90%, prompting population crashes associated with very little recruitment of new individuals and changes to intertidal communities. Habitats that were dominated by crustose coralline algae and bare rock have become dominated instead by fleshy algae and sessile invertebrates. Here, we present the first high-quality black abalone reference genome, assembled with PacBio HiFi long-reads and assembled with Dovetail Omni-C data to generate a scaffold-level assembly. The black abalone reference genome will be an essential resource in understanding the evolutionary history of this species as well as for exploring its current levels of genetic diversity and establishing future management and restoration plans.